Role of Troponin Determination to Diagnose Chest Pain in the Pediatric Emergency Department. Issue 12 (December 2021) - Brancato, Federica; De Rosa, Gabriella; Gambacorta, Alessandro; Nunziata, Alessia; Ferrara, Pietro; Buonsenso, Danilo; Covino, Marcello; Chiaretti, Antonio
Abstract : Objectives: Chest pain is a common cause to admission to the pediatric emergency department and often leads to an extensive cardiac evaluation. The objective of this study was to evaluate the usefulness of the troponin (TN) plasma level determination in the initial phase of the differential diagnosis of chest pain in children. Methods: This is a retrospective observational study on 107 patients, aged 0 to 19 years, admitted for chest pain to the pediatric emergency department of our institution. Demographics, clinical data, and patient outcomes were analyzed. Troponin values of >0.03 ng/mL but <0.1 ng/mL were considered suspected for cardiac pathology, whereas levels of >0.1 ng/mL were indicative of cardiac pathology. In these latter patients, an echocardiographic examination was also performed. Results: Only 99 patients were evaluated with electrocardiogram (ECG). In 91 of 99 patients of our series, both TN determination and ECG recording were performed. Troponin was higher than the cutoff value (0.03 ng/mL) in 9 patients (9.1%). Only 2 of the 9 patients who presented high TN values showed a nonpathological ECG, whereas 16 (17.5%) of 91 patients in whom both ECG and TN determination were performed had ECG abnormalities without a simultaneous elevation of TN. Of the 26 patients who had medical history and suggestive targets of cardiac pathology, only in 6 (23.1%) of them the diagnosis was confirmed. The final diagnosis of the 99 patients was idiopathic chest pain in 45.4% of cases. Conclusions: Even with the low cost and the relatively easiness for the plasma level determination, TN should be measured only in children with chest pain associated to familiar history suggestive of cardiovascular disease and/or clinical symptoms and/or ECG alterations.